Fostering creativity in self and the organization : your professional edge - Stein, Eric W. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2014)
The focus of this book is how to maximize your creative potential both professionally and personally. A central theme of this book is that successful creative expression is a function of hard work and discipline rather than innate talent or genius. Reaching your creative potential requires an open mind. To begin, we discuss some of mental models that facilitate or impede your development as a creative person. The book also identifies specific ways a person can accelerate his or her progress as a creative person.
1. The big picture -- 2. Know your worldview -- 3. Capitalize on your strengths -- 4. Cultivate your improvisational capacity -- 5. Develop your design proficiency -- 6. Expand your scientific and experimental mind -- 7. Deepen your aesthetic awareness -- 8. A plan for action -- Appendix -- Notes -- References -- Index.
Part of: 2013 digital library.
Includes bibliographical references (pages 133-136) and index.
Title from PDF title page (viewed on January 25, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Creative ability in business; creativity; career management; personal development; improvisation; design; experimentation; aesthetics; learning; leadership; management; worldviews; mental models; IQ; intelligence; strengths; Electronic books